Medium modulated oxygen reduction activity of Fe/Co active centre-engrafted electrocatalysts - Kashyap, Varchaswal; Anand, Aljo; Soni, Roby; Sreekumar, Kurungot (ChemElectroChem, 2019)
Iron and cobalt metal atoms are effective active centers for the synthesis of carbon-based noble-metal-free catalysts for the oxygen reduction reaction (ORR) owing to their cost-effective intrinsic activity and tunable properties. Annealing of the active center with the conducting carbon enhances the ORR activity significantly. Herein, we have engrafted Fe and Co active centers in the homemade conducting carbon and the ORR performance has been closely observed under acidic and basic pH conditions to understand the influence of the medium and participating moieties towards the performance. In the half-cell reaction, the onset potential and half-wave potential for ORR are governed by the surface intermediates and concomitantly driven by the adsorption energies of the intermediates over the active centers. The iron and cobalt active center-engrafted carbon catalyst behaves differently in acidic and basic electrolytes owing to the dissociation of the surface intermediates. The iron-based catalyst shows improved onset potential against the cobalt-based one. Similarly, the cobalt-based catalyst shows improved half-wave potential against the iron active-center-grafted catalyst. The combined synergistic effect of the two catalysts is realized in the composition represented as Fe/2Co-N-GVC, where improved onset and half-wave potentials are noted in basic medium. A significant variation in the activity of the catalyst is observed as the medium changes from acidic to basic and the effect is directly associated with the surface adsorption of the intermediates.
Keywords: active centers; half-wave potential; Mechanism; oxygen reduction reaction; transition state